Loss to follow-up of patients after antiviral treatment as an additional barrier to HCV elimination - Dorota Zarębska-Michaluk; Michał Brzdęk; Olga Tronina; Justyna Janocha-Litwin; Marek Sitko; Anna Piekarska; Jakub Klapaczyński; Anna Parfieniuk-Kowerda; Barbara Sobala-Szczygieł; Magdalena Tudrujek-Zdunek; Łukasz Laurans; Robert Flisiak (BMC Medicine)
Abstract Background Eliminating hepatitis C virus (HCV) infections is a goal set by the World Health Organization. This has become possible with the introduction of highly effective and safe direct-acting antivirals (DAA) but limitations remain due to undiagnosed HCV infections and loss of patients from the cascade of care at various stages, including those lost to follow-up (LTFU) before the assessment of the effectiveness of the therapy. The aim of our study was to determine the extent of this loss and to establish the characteristics of patients experiencing it. Methods Patients with chronic HCV infection from the Polish retrospective multicenter EpiTer-2 database who were treated with DAA therapies between 2015 and 2023 were included in the study. Results In the study population of 18,968 patients, 106 had died by the end of the 12-week post-treatment follow-up period, and 509 patients did not report for evaluation of therapy effectiveness while alive and were considered LTFU. Among patients with available assessment of sustained virological response (SVR), the effectiveness of therapy was 97.5%. A significantly higher percentage of men (p<0.0001) and a lower median age (p=0.0001) were documented in LTFU compared to the group with available SVR assessment. In LTFU patients, comorbidities such as alcohol (p<0.0001) and drug addiction (p=0.0005), depression (p=0.0449) or other mental disorders (p<0.0001), and co-infection with human immunodeficiency virus (HIV) (p<0.0001) were significantly more common as compared to those with SVR assessment. They were also significantly more often infected with genotype (GT) 3, less likely to be treatment-experienced and more likely to discontinue DAA therapy. Conclusions In a real-world population of nearly 19,000 HCV-infected patients, we documented a 2.7% loss to follow-up rate. Independent predictors of this phenomenon were male gender, GT3 infection, HIV co-infection, alcohol addiction, mental illnesses, lack of prior antiviral treatment and discontinuation of DAA therapy.